Binge Drinking and Antisocial and Unlawful Behaviours in Australia1. Issue 297 (24th February 2016) - Yang, Ou; Zhao, Xueyan; Srivastava, Preety
Abstract : This paper presents individual‐level evidence from Australia to examine the factors associated with binge drinking and several alcohol‐related antisocial and unlawful behaviours. We study in particular the role of binge drinking in increasing the likelihood of engaging in these negative behaviours. We use individual‐level data from a national representative survey and a system econometric model that allows unobservable factors for all negative behaviours to be correlated. Potential misclassification of individuals' drinking pattern is accounted for. We find evidence of under‐reporting for bingeing and significant effects of binge drinking on drink‐driving, physical and verbal abuse, public disturbance, and stealing and damaging property.